Питання визначення початкового моменту кримінально-правової охорони життя людини - Байлов, А. В.; Bailov, A. V. (Право і безпека. - 2014. - № 1(52). - С. 76-80, 2014)
Проаналізовано існуючі в теорії кримінального права спірні позиції учених щодо визначення початкового моменту кримінально-правової охорони життя людини. Запропоновано зміни до чинного кримінального законодавства.

The scholars’ disputed positions existing in the theory of criminal law concerning the definition of the initial moment of criminal and legal protection of human life are analyzed. Determining the initial moment of criminal and legal protection of human life, first of all allows correctly classify crimes against human life and health, distinguish homicide from an act that does not have the elements of a crime, and illegal abortion. Besides, it makes possible to avoid court mistakes according to criminal proceedings of this category of cases. It is stated that the more lawyers define the beginning of criminal and legal protection of human life, the more there are different positions in the theory of criminal law. The statement that the initial moment of human life is the emergence of any part of a child’s body from the womb during the childbirth (or while cesarean), when there is an objective possibility to harm a child’s body, has received the further development. Medical and legal aspects regarding human life origin are analyzed; it is concluded that the beginning of human life from a legal point of view is the birth (formation) of the brain, namely, accomplishment of the full 22 weeks of fetal development by a fetus. Since this moment there is a right for a life and should begin his/her criminal and legal protection. Alterations to the current criminal legislation are offered, namely Section II of the Special Part of the Criminal Code of Ukraine is proposed to supplement with the Article 115-1 entitled «Encroachment on the viable human fetus».

Проанализированы существующие в теории уголовного права спорные позиций учёных относительно определения начального момента уголовно-правовой охраны жизни человека. Предложены изменения в действующее уголовное законодательство.
The issue of defining the initial moment of the criminal and legal protection of human life
Вопросы определения начального момента уголовно-правовой охраны жизни человека
Keywords: життя людини; початок життя людини; людський плід; кримінально-правова охорона; умертвління плода людини; human life; beginning of human life; human fetus; criminal and legal protection; devitalization of the human fetus; жизнь человека; начало жизни; человеческий плод; уголовно-правовая охрана; умертвление плода человека